ANALISIS KUALITAS AIR SUNGAI AKIBAT PENCEMARAN TEMPAT PEMBUANGAN AKHIR SAMPAH BATU BOLA DAN KARAKTERISTIK SERTAKELUHAN KESEHATAN PENGGUNA AIR SUNGAI BATANG AYUMI DI KOTA PADANGSIDIMPUAN TAHUN 2012 - Alprida Harahap; evi Naria; Devi Nuraini Santi (Lingkungan dan Kesehatan Kerja, 2013)
Analysis of river water quality due to Batu Bola landfill pollution and characteristics with health  of Batang Ayumi river users in Padangsidimpuan city. Batang Ayumi river which located in Batunadua village, district Batunadua, Padangsidimpuan city, has been polluted by Batu Bola landfills, according to government regulation No.82 of  2001 concerning about the Management of  Water Quality and Water Pollution Control. This study is a descriptive survey, which is to know about the physical pollution (TDS) and chemical pollution (BOD, COD and Phosphate) in Batang Ayumi river, taken from 10 points whitin 50 meters, and river users health problems were conducted in 2012. Object of this research is the river. Batu Bola landfills and mix between the outlet and river water are the comparison samples in the lab. The result of this research showed the contamination of TDS and BOD in all samples, but only a few samples indicated COD and Phosphate contamination from all the samples studied. The highest result is the landfill outlet, which is TDS 3140 mg/l, BOD 31,63 mg/l, COD 87,8 mg/l and Phosphate 0,5 mg/l. The result of interview show that  there is many people who suffer skin desease and eye desease. Local government is advised to give more attention to the Batu Bola landfills so that people are safer in using the river water for their daily needs, because many people are still dependent on Batang Ayumi river. Key words : River water, Pollution, Trash, Desease